T Follicular Helper Cell Subsets and the Associated Cytokine IL-21 in the Pathogenesis and Therapy of Asthma - Gong, Fang; Zheng, Ting; Zhou, Pengcheng (Frontiers in Immunology, 2019)
For many decades, T helper 2 (TH2) cells have been considered to predominantly regulate the pathogenic manifestations of allergic asthma, such as IgE-mediated sensitization, airway hyperresponsiveness, and eosinophil infiltration. However, recent discoveries have significantly shifted our understanding of asthma from a simple TH2 cell-dependent disease to a heterogeneous disease regulated by multiple T cell subsets, including T follicular helper (TFH) cells. TFH cells, which are a specialized cell population that provides help to B cells, have attracted intensive attention in the past decade because of their crucial role in regulating antibody response in a broad range of diseases. In particular, TFH cells are essential for IgE antibody class-switching. In this review, we summarize the recent progress regarding the role of TFH cells and their signature cytokine interleukin (IL)-21 in asthma from mouse studies and clinical reports. We further discuss future therapeutic strategies to treat asthma by targeting TFH cells and IL-21.